Does a linear position transducer placed on a stick and belt provide sufficient validity and reliability of countermovement jump performance outcomes? - Vladimír Hojka; Petr Šťastný; James J. Tufano; Dan Omcirk; Martin T. Janikov; Martin Komarc; Radim Jebavý (Termedia Publishing House, 2021)
Manufacturers recommend that linear position transducers (LPTs) should be placed on the side of a barbell (or wooden dowel) to measure countermovement jump (CMJ) height, but the validity and reliability of this placement have not been compared to other attachment sites. Since this recommended attachment site is far from the centre of mass, a belt attachment where the LPT is placed between the feet may increase the validity and reliability of CMJ data. Thirty-six physical education students participated in the study (24.6 ± 4.3 years; 177.0 ± 7.7 cm; 77.2 ± 9.0 kg). Parameters from the two LPT attachments (barbell and belt) were simultaneously validated to force plate data, where the nature of bias was analysed (systematic vs random). The within-session and between-session reliability of both attachment sites were compared to force plate data using a test-retest protocol of two sets of 5 CMJs separated by 7 days. The LPT provided highly reliable and valid measures of peak force, mean force, mean power, and jump height, where the bias was mostly systematic (r2 > 0.7; ICC > 0.9). Peak velocity, mean velocity, and peak power were in very good agreement with the force plate and were highly reliable (r2 > 0.5; ICC > 0.7). Therefore, both attachment sites produced similar results with a systematic bias compared to force plate data. Thus, both attachment sites seem to be valid for assessing CMJs when the measuring tool and site remain consistent across measurements. However, if LPT data are to be compared to force plate data, recalculation equations should be used.